2014
DOI: 10.1017/s1368980014002067
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status as assessed by nutrient intakes and biomarkers among women of childbearing age – is the burden of nutrient inadequacies growing in America?

Abstract: Objective: Understanding nutrient intakes among women of childbearing age within the USA is important given the accumulating evidence that maternal body weight gain and nutrient intakes prior to pregnancy may influence the health and well-being of the offspring. The objective of the present study was to evaluate nutritional status in women of childbearing age and to ascertain the influence of ethnicity and income on nutrient intakes. Design: Nutritional status was assessed using data on nutrient intakes throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 37 publications
4
23
0
Order By: Relevance
“…Recent studies have raised concerns regarding nutrient intake in the United States, especially with regard to vitamin A and vitamin A precursors from fruits and vegetables. Data from 2003 to 2008 NHANES cycles demonstrate that women of childbearing age in the United States are not meeting nutrient guidelines for vitamin A intake, with distinct differences present between ethnic groups and socioeconomic strata [20,31,32]. Lower income individuals consumed lower quality foods when compared to those with higher incomes, including fruits and vegetables, as measured by the Alternate Healthy Eating Index [33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have raised concerns regarding nutrient intake in the United States, especially with regard to vitamin A and vitamin A precursors from fruits and vegetables. Data from 2003 to 2008 NHANES cycles demonstrate that women of childbearing age in the United States are not meeting nutrient guidelines for vitamin A intake, with distinct differences present between ethnic groups and socioeconomic strata [20,31,32]. Lower income individuals consumed lower quality foods when compared to those with higher incomes, including fruits and vegetables, as measured by the Alternate Healthy Eating Index [33].…”
Section: Discussionmentioning
confidence: 99%
“…We categorized PIR into ≤1.85 and >1.85 based on previous studies [20], or income that is 185% of the poverty threshold applied by the Food and Nutrition Service. The PIR is the ratio of household income to the poverty threshold after accounting for inflation and family size [21,22].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recently concerns have been raised about the diet quality of susceptible populations. A study using data from the 2003-2008 National Health and Nutrition Examination Survey (NHANES), which is considered a representative sample of the United States population, demonstrated that women of childbearing age in the United States are not consuming adequate amounts of vitamin A [44]. This is especially true for women in minority ethnic groups, as well as women of lower socioeconomic status [44].…”
Section: Journal Of Clinical Nutrition and Dietetics Issn 2472-1921mentioning
confidence: 99%
“…A study using data from the 2003-2008 National Health and Nutrition Examination Survey (NHANES), which is considered a representative sample of the United States population, demonstrated that women of childbearing age in the United States are not consuming adequate amounts of vitamin A [44]. This is especially true for women in minority ethnic groups, as well as women of lower socioeconomic status [44]. In general, lower income individuals have less access to high quality, vitamin A-rich foods such as fruits and vegetables, as measured by the Alternate Healthy Eating Index, which is a summary score of 11 components that measures diet quality.…”
Section: Journal Of Clinical Nutrition and Dietetics Issn 2472-1921mentioning
confidence: 99%